Engineering strategies for high‐voltage LiCoO2 based high‐energy Li‐ion batteries - Xiaoshuang Ma; Jinkun Wang; Zehua Wang; Li Wang; Hong Xu; Xiangming He (Electron)
Abstract To drive electronic devices for a long range, the energy density of Li‐ion batteries must be further enhanced, and high‐energy cathode materials are required. Among the cathode materials, LiCoO2 (LCO) is one of the most promising candidates when charged to higher voltages over 4.3 V. However, high‐voltage LCO materials are confronted with severe surface and bulk issues inducing poor cyclic stability. To completely unleash the potential of LCO cathodes, a more comprehensive theoretical understanding of the underlying issues is necessary, along with active exploration of previous modifications. This paper mainly presents the degradation mechanisms of LCO under high voltage, the formation and evolution mechanisms of the cathode electrolyte interface, and the surface engineering strategies employed to enhance the cell performance. By organizing and summarizing these modifications, this work aims to establish associations among common research issues and to suggest future research priorities, thus facilitating the rapid development of high‐voltage LCO.